Jerry Lee Lewis : the definitive collection [compact disc] - Lewis, Jerry Lee (Hip-O, 2005)
With his explosive piano style and crazy reputation Jerry Lee Lewis earned his nickname the Killer. Twenty-four of his best songs, including six number one hits, are together to create a definite collection.